2014
DOI: 10.1016/j.molcel.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Translocations in Human Cells Are Generated by Canonical Nonhomologous End-Joining

Abstract: Summary Breakpoint junctions of the chromosomal translocations that occur in human cancers display hallmarks of nonhomologous end-joining (NHEJ). In mouse cells, translocations are suppressed by canonical NHEJ (c-NHEJ) components, which include DNA ligase IV (LIG4), and instead arise from alternative NHEJ (alt-NHEJ). Here we used designer nucleases (ZFNs, TALENs, and CRISPR/Cas9) to introduce DSBs on two chromosomes to study translocation joining mechanisms in human cells. Remarkably, translocations were alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
275
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 302 publications
(296 citation statements)
references
References 66 publications
19
275
2
Order By: Relevance
“…Using cell lines selectively compromised in different components of NHEJ repair, we have identified a crucial role for LIG4 in mediating long-range inter-chromosomal fusions between damaged telomeres and diverse genomic locations. Consistent with the hallmarks of C-NHEJ (Ghezraoui et al 2014;Oh et al 2014), these telomere-genomic interactions showed reduced microhomology usage at junctions in comparison with intra-chromosomal telomere fusion events. Although the frequency of telomere-genomic events was severely reduced in cells lacking LIG4, there was no analogous impact on intra-chromosomal fusion events, resulting in a notable homogeneity of parameters examined among all samples.…”
Section: A-and C-nhej Of Dysfunctional Human Telomeressupporting
confidence: 64%
See 1 more Smart Citation
“…Using cell lines selectively compromised in different components of NHEJ repair, we have identified a crucial role for LIG4 in mediating long-range inter-chromosomal fusions between damaged telomeres and diverse genomic locations. Consistent with the hallmarks of C-NHEJ (Ghezraoui et al 2014;Oh et al 2014), these telomere-genomic interactions showed reduced microhomology usage at junctions in comparison with intra-chromosomal telomere fusion events. Although the frequency of telomere-genomic events was severely reduced in cells lacking LIG4, there was no analogous impact on intra-chromosomal fusion events, resulting in a notable homogeneity of parameters examined among all samples.…”
Section: A-and C-nhej Of Dysfunctional Human Telomeressupporting
confidence: 64%
“…This result distinguishes intra-chromosomal from inter-chromosomal fusions that demonstrate greater dependency on LIG4 (Ghezraoui et al 2014). …”
Section: −/−mentioning
confidence: 89%
“…Microhomology Mediated End Joining (an alternative NHEJ pathway) leads to the deletion of the sequence between microhomologies (reviewed in 2 ). In addition, recent studies suggest that NHEJ is the primary cause of translocations 3,4 and dysfunctional telomeres fusion. 5 Finally, while HR pathways can be entirely conservative when the sister chromatid is used as a template, dramatic events such as repeat amplification/deletion or loss of heterozygosity (LOH) can occur when HR operates on repeated sequences or homologous chromosomes, respectively.…”
Section: Homologous Recombination and Non Homologous Endmentioning
confidence: 99%
“…DNA double-strand breaks (DSBs) occurring on two chromosomes induce translocations (8)(9)(10)(11)(12), a process primarily mediated by nonhomologous end joining (NHEJ), a nonconservative DNA repair pathway that involves the joining of DNA ends without the involvement of extensive homology (1,13). DSB generation in early model studies was achieved through the introduction of I-SceI endonuclease cleavage sites at two genomic loci, expression of I-SceI, and then selection for the translocation using preintroduced marker fragments (8)(9)(10).…”
mentioning
confidence: 99%
“…More recently, the discovery of RNAguided nucleases in bacterial adaptive immunity (CRISPR-Cas9) has facilitated DSB introduction at desired genomic loci (18,19). Using these various programmable nucleases, a number of cancer translocations have been generated in a variety of human cell lines, including EWSR1-FLI1 (ZFNs, CRISPR-Cas9) (11,20,21), NPM1-ALK (TALENs, CRISPR-Cas9) (11,12), and CD74-ROS1 (CRISPR-Cas9) (22). Oncogenic chromosomal inversions have also been engineered in mouse tissues, leading to tumorigenesis (EML4-ALK) (23).…”
mentioning
confidence: 99%